THE IMPLEMENTATION OF TASK-BASED INSTRUCTION IN EFL TEACHING SPEAKING SKILL - Hanif Nurcholish Adiantika; Halim Purnomo (Indonesian EFL Journal, 2018)
The present study aims to examine the implementation of task-based instruction in EFL teaching speaking skill. It covers the advantages and shortcomings faced by teachers and students in implementing task-based instruction particularly in teaching speaking skill. This study employs a qualitative approach by using a case study design. This study was initiated in one of senior high school in Kuningan covering one class of eleventh grade students. The data were obtained through interview and questionnaires. The findings showed that task-based instruction result in several advantages and shortcomings. It was found that task-based instruction enables students to be more active in teaching and learning process and it was also proven to enhance students’ speaking skill. Meanwhile, there were also some shortcomings identified in this study i.e. teacher’s ability, time availability, and different students’ proficiency level. Therefore, it is suggested to implement task-based instruction in a long time period and in a very proper way by considering different students’ ability inside a certain classroom.Keywords: task-based instruction; teaching speaking skill; advantages and shortcomings of task-based instruction.